Antitumor Cannabinoid Chemotypes: Structural Insights - Morales, Paula; Jagerovic, Nadine (Frontiers in Pharmacology, 2019)
Cannabis has long been known to limit or prevent nausea and vomiting, lack of appetite and pain. For this reason, cannabinoids have been successfully used in the treatment of some of the unwanted side effects caused by cancer chemotherapy. Besides their palliative effects, research from the past two decades has demonstrated their promising potential as antitumor agents in a wide variety of tumors. Cannabinoids from endogenous, phytogenic and synthetic nature have shown to impact the proliferation of cancer through the modulation of different proteins involved in the endocannabinoid system such as the G protein-coupled receptors CB1, CB2, and GRP55, the ionotropic receptor TRPV1, or the fatty acid amide hydrolase FAAH. In this article we aim to structurally classify the antitumor cannabinoids chemotypes described so far according to their targets and types of cancer. In a drug discovery approach, their in silico pharmacokinetic profile has been evaluated in order to identify appropriate drug-like profiles which should be taken into account for further progress towards the clinic. This analysis may provide structural insights into the selection of specific cannabinoid scaffolds for the development of antitumor drugs for the treatment of particular types of cancer.